Is it human mind attuned with general ecological principles? - Corral-Verdugo, Victor; García-Vazquez, Fernanda Inez; Fraijo-Sing, Blanca; Tapia-Fonllem, Cesar (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2018)
Some scholars claim that similarities exist between human communities and ecosystems; also, that people can learn how to live sustainably from knowing the way ecosystems work. Yet, at the psychological level, the relationship between practicing sustainable behaviors and living in accordance with ecological principles has been barely studied. This paper addresses such relationship, testing the idea that acting in accordance with ecological principles requires 1) a knowledge of ecological rules, 2) an affinity towards those rules, and 3) behaving accordingly (i.e., acting sustainably). We call this hypothetical construct the Human Attunement with Ecological Principles (HAEP), assuming that it implies the presence of a human predisposition to knowing, valuing and applying these principles. In developing the idea, the paper reviews relevant literature, aiming to find evidence that supports the HAEP hypothesis, and presents results of a study showing that HAEP significantly and saliently predicts engagement in sustainable behaviors.